Reflections on the current dentistry professional education in Colombia (Revista Nacional de Odontología, 2020)
Currently, professional education on dentistry in Colombia is worrying, not because of teaching quality, but because this human resource is going through a precariousness time that could be contained if the country reflects on why educate oral health professionals when there are no employment possibilities or not access to well paid jobs that doesn’t allow to recover the investment done. This article aims to provoke that national and education authorities make a accurate planification of health human resources as the WHO and OPS havedemanded over the years.
Keywords: university education; dentistry; dentists; employability